Mehr Nachwuchs bei Nutzfischarten der Nordsee, ausser beim Kabeljau - Dornheim, Holger; Wegner, Gerd (2000)
Ninety-one half-hour tows with the Grande Ouverture Verticale bottom trawl (GOV), 111 hydrographic stations and 100 catches with the Methot-Isaac-Kidd Net (MIK) were this years’ contribution of “Walther Herwig III” to the IBTS in various areas of the North Sea. Preliminary results indicate that especially haddock and, to some extent,whiting and Norway pout generated an ample 1999 yearclass. Indices for herring are also well above last years’ index whereas the cod indices indicate no substantial improvementof the stock. Largest concentrations of herring larvae were found in Moray Firth and west of the Dogger Bank/The Gut area. Temperatures of the North Sea were found to be above the long term means: 1 Centigrade on the open sea and up to 3 Centigrades in coastal areas. This years’ “WH III” IBTS activities at sea were considerably hampered by rough weather